SKRINING DAN UJI AKTIVITAS ANTIBAKTERI BEBERAPA RUMPUT LAUT DARI PANTAI BATU BOLONG CANGGU DAN SERANGAN - Maduriana, I Made; Sudira, I Wayan (Buletin Veteriner Udayana; Vol. 1 No. 2 Agustus 2009, 2012)
In this study, extracts of seaweeds Gracilaria arculata zanardinifrom Batu Bolong, Cangguand Gracilaria lichenoides (Linnaneus) and Hypnea sp. fromSerangan were screened forthe production of antibacterial against E. coli and M.luteus.The result of the study showed that all species of seaweeds have activity against E.coli and M. luteus, but Gracilaria arculata zanardini was the species of seaweed in thestrongest activity against E. coli and M. luteus.
Keywords: Screening; antibacterial activity; seaweeds